Development and Validation of the Knowledge, Attitudes, and Practice Purification (‘Tahara’) Questionnaire among Jordanian Muslims - Basim Aldahadha; Asma Saraireh (Islamic Guidance and Counseling Journal, 2026)
This study aimed to assess the validity of the Knowledge, Attitudes, and Practice questionnaire on purity among Muslims. Purity is a religious requirement that must be met for most acts of worship to be accepted. To develop the questionnaire, it was administered to a sample of 7 reviewers and 290 participants. The procedures consisted of two stages. The first stage was to build the tool’s items from previous literature. The second stage was to judge the tool through content validity. Three equations were used: the content validity ratio, scale-level content validity index, and item-level content validity index, in addition to exploratory factor analysis (EFA) and reliability via test-retest and internal consistency. The results of the first stage showed that the questionnaire in its initial form consisted of 3 factors with a total of 81 items. After applying the content validity equations, it became clear that 17 items had a percentage of less than 99%, so they were deleted, and the number of items became 64. When EFA was conducted, 15 items were deleted, and the loading level was less than 0.4; thus, 49 questionnaire items were distributed across the three factors: practice (n=15), attitudes (n=18), and knowledge (n=16). The study concluded that the KAP questionnaire can be applied to Muslims' purity as a religious belief in maintaining public health, along with a religious requirement.